SUNDANESE ISOGLOSSES OF LEXICAL VARIATION IN KUNINGAN - Fahmy Hygienis (University of Kuningan, 2013)
Abstract: This article discussed the distribution of lexical variation in 32 districts of Kuningan. The study was conducted to uncover dialect maps in Kuningan, their isogloss lines, and also major lexical variations.The study employed descriptive design. The data were collected from 32 respondents by using two methods, questionnaire and interview. Each respondent represents one district of Kuningan. By using judgment sampling technique, the respondents were chosen.Â The data were analyzed in three ways: populating the data, mapping the data and describing the map. As the result, the study revealed 30 dialect maps in Kuningan. The maps described the distributions of 135 lexical variations and the isogloss lines. The isoglosses lines are mostly overlapped with the others. 70% of the maps indicate that there are â€œoverlapping isoglossesâ€. This indicates that every district in Kuningan has more than one lexical variation in describing one signiï¬ed. Based on the maps; it was also found that the isogloss lines were mostly overlapping. It means that, most of Kuningan people tend to use different lexical variations compared to their surrounding districts. Besides, it was also found that there were ï¬ve major lexical variations used by the Kuningans.Keywords: dialect, lexical variation, isogloss.